Exposure Behaviors and Factors Affecting Animation Cartoon of Youth - Mongkhonsin, Khunanon; Suyanang, Thanhathai; Phakanon, Natchapol; Tirakoat, Suwich; Hiruncharoenvate, Chaya (Journal of Applied Informatics and Technology, 2019)
Animated cartoon is so significantly impactful to children and youth that it easily creates imitation behaviors among its audience. This research aims to 1) study the acceptance and imitation behaviors among youth 2) analyze the elements that form the factors influencing youth’s imitation behavior 3) compare the differences between these factors between various gender and age range. The data was collected from 175 students majoring in Computer Animation and Game at the Faculty of Informatics, Mahasarakham University. The survey used had the confidence level at 95%. The statistics used in this research was frequency, percentage, mean, standard deviation, t-test, F-test, and Varimax rotation. The results showed that the participants were mostly youth of age under 20 years old. The reported benefits from watching animated cartoon were promoting creativity and relaxing, causing participants to repeatedly watch the same story for 1-3 times. The imitation behavior approximately started at the age of 9, and the numbers of those who still imitate behaviors from the animated cartoon and those who don’t are not significantly different from each other. The analysis showed that the factors affecting the imitation behaviors were 1) the identity design of cartoon characters and 2) the compelling storytelling of the story. Moreover, the difference in gender doesn’t significantly affect these factors.